'It's a man's world': the lived experiences of women working in the New Zealand professional commercial property industry. Issue 2 (3rd April 2022) - Levy, Deborah; Plester, Barbara; Hills, Raewyn; Horan, Jane
ABSTRACT: Gender diversity in the workplace results in the increased effectiveness of an organisation. However, within the commercial property profession in many countries including New Zealand (as in a number of other professions), only a small number of women are reaching senior positions. This research investigates why this might be. The study comprises one-to-one in-depth interviews with women currently working or who have previously worked in the commercial property profession in Auckland, New Zealand, to develop an understanding of what forces are at play in women's choices to participate in the commercial property industry in Auckland – or not. Common lived experiences are identified including passion for the industry and the importance of an effective human resources department, they demonstrate gender imbalance, issues around having children, and difficulties around promotions and wage negotiations. Common challenges were workplace bullying, attitudes towards women, socialising, 'fitting-in' and coping with male banter. The study concludes that women working in the commercial property profession in New Zealand have thrived through mentorship, taking ownership of their careers and finding a good employer. The insights as to how women perceive the professional commercial property industry can be used to increase effectiveness by increasing gender diversity and inclusion.